The evolution of fossoriality and the adaptive role of horns in the Mylagaulidae (Mammalia: Rodentia) - Hopkins, Samantha S.B (The Royal Society, 2005)
Ceratogaulus, a member of the extinct fossorial rodent clade Mylagaulidae, is the only known rodent with horns and the smallest known horned mammal. The function of the large, dorsally projecting nasal horns on this burrowing animal has been the subject of wide speculation among palaeontologists; suggested uses range from sexual combat to burrowing. Mammals have evolved adaptations for digging repeatedly; horns and other cranial appendages have also evolved numerous times. These two adaptations co-occur in mammals extremely rarely: only two fossil genera (Ceratogaulus and the xenarthran Peltephilus) and no extant mammals are both horned and fossorial. Tracing the evolution of fossoriality in aplodontoid rodents (the larger clade to which Ceratogaulus belongs) reveals that Ceratogaulus descended from ancestors who dug by head-lifting. Whereas this suggests an obvious explanation for the horns of this rodent, evidence from functional morphology, anatomy, phylogeny and geologic context indicates that the horns in Ceratogaulus were used for defence, rather than digging, and evolved to offset increased predation costs associated with spending more time foraging above ground as body size increased.